2022
DOI: 10.3390/en15228743
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Vibration of Non-Rotating Structures of a High-Head Pump-Turbine during Start-Up in Turbine Mode

Abstract: Pumped storage-power plants play an extremely important role in the modern smart grid due to their irreplaceable advantages in load peak-valley regulation, frequency modulation, and phase modulation. The number of start-stops per day of pump-turbine units is therefore also increasing. During the start-up transient process in turbine mode, the complex flow in runner passage, crown and band chambers, and seal labyrinth is able to induce severe vibration of non-rotating structures such as head cover, stay-ring, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, some scholars adopt the research method of combining the one-dimensional characteristic line method with the three-dimensional flow calculation, and use the inlet and outlet hydraulic characteristics such as pressure and flow rate obtained from the one-dimensional calculation of the pipeline as the boundary conditions of the three-dimensional flow calculation of the unit, so as to realize the solution of the structural response of the unit. [21,22]. Researchers have further confirmed the reliability of the numerical investigation according to the field measurement data for the turbine start-up of the pump-turbine units [23,24].…”
Section: Introductionmentioning
confidence: 66%
“…Therefore, some scholars adopt the research method of combining the one-dimensional characteristic line method with the three-dimensional flow calculation, and use the inlet and outlet hydraulic characteristics such as pressure and flow rate obtained from the one-dimensional calculation of the pipeline as the boundary conditions of the three-dimensional flow calculation of the unit, so as to realize the solution of the structural response of the unit. [21,22]. Researchers have further confirmed the reliability of the numerical investigation according to the field measurement data for the turbine start-up of the pump-turbine units [23,24].…”
Section: Introductionmentioning
confidence: 66%
“…The fluid instability certainly has an impact on the structural components. The dynamic stress distribution of the runner blades during the start-up process 2 of the pump turbine was preliminarily analysed through short-time Fourier transform (STFT) [5], and the effects of pressure fluctuation on the structural stress and bearing thrust of the unit during the startup process of the pump turbine were studied [6]. In terms of vibration, Cao et al [7] studied the wet mode of the runner under cavitation state, found that cavitation will affect the asymmetry of the added mass matrix.…”
Section: Introductionmentioning
confidence: 99%
“…During the variable speed start-up process of a unit equipped with a FSFC, different control strategies will result in different start-up operating trajectories. When the unit operates in an operating zone with poor flow patterns, the pressure pulsations will significantly increase, leading to aggravated vibration and damage to the unit [9][10][11]. Therefore, it is necessary to discover the flow patterns and pressure pulsations that may occur in different operating conditions during the unit start-up process, in order to judge the quality of the operating conditions and avoid undesirable conditions in actual operation.…”
Section: Introductionmentioning
confidence: 99%